2020
DOI: 10.1001/jamasurg.2020.1129
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Sex-Based Disparities in Liver Allocation

Abstract: IMPORTANCE Differences in local organ supply and demand have introduced geographic inequities in the Model for End-stage Liver Disease (MELD) score-based liver allocation system, prompting national debate and patient-initiated lawsuits. No study to our knowledge has quantified the sex disparities in allocation associated with clinical vs geographic characteristics. OBJECTIVE To estimate the proportion of sex disparity in wait list mortality and deceased donor liver transplant (DDLT) associated with clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
0
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(150 citation statements)
references
References 54 publications
6
109
0
20
Order By: Relevance
“…However, the results are similar to other findings in previous publications [12], and should be a topic for future, more detailed studies. Indeed, a recent study has also shown that women are at a higher risk for death while on the transplant waiting list [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results are similar to other findings in previous publications [12], and should be a topic for future, more detailed studies. Indeed, a recent study has also shown that women are at a higher risk for death while on the transplant waiting list [23].…”
Section: Discussionmentioning
confidence: 99%
“…Females are more likely to die or be de-listed due to disease severity while on the liver transplant waitlist 8,10,12 . Concordantly, in our sample, females who had undergone a liver transplant had significantly more pre-transplant decompensation traits than males.…”
Section: Discussionmentioning
confidence: 99%
“…After controlling for estimated liver size 12,14 or height 15 , sex disparities in transplant were reduced, but not eliminated. Likewise, controlling for geographic disparities did not ameliorate the sex disparity in receiving a liver transplant 12 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…( 41 ) In a study exploring 3 contributors to disparities in waitlist survival and LT (geography, candidate anthropometric measurements, and MELD score), size mismatch between the donor and intended recipient and incorrect assessments of liver disease severity based on the MELD score were more strongly associated with the observed sex disparity in waitlist mortality than local organ supply. ( 49 ) Defining “short stature” was the focus of a recent work by Ge et al, which showed that after adjustment for clinical and demographic characteristics, height <166 cm (5 feet, 5 inches) remained associated with an 8% increased risk of waitlist mortality (95% CI, 1.03‐1.14). ( 50 ) In a recent transplant registry–based study of gender disparities in transplantation for acute liver failure, the authors found no disparity in LT between men and women waitlisted as Status 1, suggesting that Status 1 priority may mitigate gender‐based disparities in LT. ( 51 )…”
Section: Disparities In the Lt Care Cascadementioning
confidence: 99%